RETRACTED: Relationship between serum TGF- β 1, MMP-9 and IL-1β and pathological features and prognosis in breast cancer - Cai, Shuyan; Zheng, Jianwei; Song, Huimin; Wu, Haoliang; Cai, Wang (Frontiers in Genetics, 2023)
To investigate the levels of serum transforming growth factor-β 1 (TGF-β1), Matrix metalloproteinase-9 (MMP-9) and Interleukin-1 β (IL-1 β) in breast cancer (BC), and analyzing their relationship with pathological features and prognosis. Retrospective analysis of 86 subjects with BC (BC subgroup) and another 50 healthy subjects (control subgroup) during the same period were included. The clinical data were collected. In this research, in BC subgroup, The levels of serum TGF- β 1, MMP-9 and IL-1 β were significantly higher than those in control subgroup. The levels of TGF- β 1 and MMP-9 in serum of BC subjects was correlated with clinical stage, histological grade, lymph node metastasis and molecular classification, but not with age, tumor size and menopausal status. The level of serum IL-1 β was related to tumor size, clinical stage, histological grade and lymph node metastasis. Multivariate Logistic regression analysis showed that the high level of serum TGF- β1 and MMP-9 was independent risk factors for BC. High level of serum IL-1 β was not an independent risk factor for BC. The 3-year disease-free survival rate in high TGF- β1 subgroup and high MMP-9 subgroup was significantly lower than that in low TGF- β 1 subgroup and low MMP- 9 subgroup. To conclude, serum TGF- β 1, MMP-9 and IL-1β are highly expressed in BC, and the subjects with elevated serum levels of TGF- β 1 and MMP-9 suggests poor prognosis.